DNA damage in patients infected by Helicobacter pylori - Ladeira, Marcelo S.P. [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Salvadori, Daisy M.F. [UNESP]; Queiroz, Dulciene M.M.; Freire-Maia, Dértia V. [UNESP] (My University, 2004)
Helicobacter pylori (H. pylori) is considered to predispose carriers to gastric cancer but its role on gastric carcinogenesis is still unknown. The aim of this study was to investigate DNA damage by the comet assay in gastric epithelial cells from antrum and corpus in H. pylori-infected patients with gastritis of different degrees. H. pylori status, gastric histology, and DNA damage were studied in 62 H. pylori-infected and 18 non-infected patients, all of them non-smokers, non-alcoholics, and non-drug users. DNA damage was significantly higher in H. pylori-infected patients presenting gastritis than in non-infected patients with normal mucosa. A direct correlation between the levels of DNA damage and the intensity of gastritis was observed in H. pylori-infected patients. Association between DNA damage and age was also found. The levels of DNA damage were significantly higher in patients older than 50 years than in younger patients with the same degree of gastritis. Our results indicate that H. pylori infection is associated with DNA damage in gastric epithelial cells, which could be a biomarker of risk for gastric cancer in humans.